Analisis Bid-Ask Spreads, Market Value, dan Variance Return Pada Holding Period - Erna Apriani; Akfika Rizky Sabilla; Abdul Latif (Universitas 45 Surabaya, 2023)
Holding shares that have been purchased by investors is a level of trust in the company itself, and whether or not investors hold their shares for a long time greatly influences the condition of the holding period. During a period of transition and global economic uncertainty, stock prices in the energy sector are a long-term alternative to be maintained. Thus this study aims to analyze the effect of bid-ask spreads, market value, and variance returns on the holding period of the energy sector. The data used in this study is secondary data in the form of data on the number of outstanding shares, daily data on the volume of stock trading transactions, the bid price and ask price of shares, and the average stock return of energy sector companies during 2020-2021 with the type of time series data. The population and sample in this study are all companies going public in the energy sector on the Indonesian stock exchange, namely 58 companies on all accelerator boards for the period 2020-2021. The data analysis tool used is a multiple linear regression model to look for the effect of bid-ask spreads on market value and variance return on the holding period. The results of this study show that the bid-ask spreads variable has a negative effect on the holding period, and for market value variable results, the variance return does not affect the holding period.